1936
DOI: 10.1098/rspb.1936.0017
|View full text |Cite
|
Sign up to set email alerts
|

The action of sodium nitrate upon the infection of Lucerne root-hairs by nodule bacteria

Abstract: [Plates 11, 12]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

1937
1937
2002
2002

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 3 publications
1
16
0
Order By: Relevance
“…IAA increases the plasticity of cell walls (Galston & Purves, 1960), and is produced by nodule bacteria (Link, 1937;Kefford, Brockwell & Zwar, 1960). According to Thornton (1936) the deformation of root hairs, which is believed to be caused by bacterial IAA, is a necessary prelude to infection. However, our present knowledge of the action of IAA on cell walls-which might involve an immobilization of pectin methylesterase (Glasziou, 1957;Fiihraeus & Ljunggren, 1959)-are too vague to permit detailed conclusions about the role of…”
Section: Discussionmentioning
confidence: 99%
“…IAA increases the plasticity of cell walls (Galston & Purves, 1960), and is produced by nodule bacteria (Link, 1937;Kefford, Brockwell & Zwar, 1960). According to Thornton (1936) the deformation of root hairs, which is believed to be caused by bacterial IAA, is a necessary prelude to infection. However, our present knowledge of the action of IAA on cell walls-which might involve an immobilization of pectin methylesterase (Glasziou, 1957;Fiihraeus & Ljunggren, 1959)-are too vague to permit detailed conclusions about the role of…”
Section: Discussionmentioning
confidence: 99%
“…In spinach (Spinacea oleracea), root hair length was 7-fold higher at 0.01 mM NO 3 − compared to 1 mM (Foehse and Jungk, 1983). Foehse and Jungk did not report the effect of NO 3 − on root hair density, but other studies have shown negative effects on root hair numbers in oil-seed rape (Bhat et al, 1979), alfalfa (Medicago sativa) (Thornton, 1936) and Casuarina cunninghamiana (Kohls and Baker, 1989).…”
Section: Root Hair Length and Densitymentioning
confidence: 99%
“…There are many reports that root hair development is also negatively affected by the NO 3 − supply (Boot and Mensink, 1990;Foehse and Jungk, 1983;Kohls and Baker, 1989;Robinson and Rorison, 1987;Thornton, 1936). In spinach (Spinacea oleracea), root hair length was 7-fold higher at 0.01 mM NO 3 − compared to 1 mM (Foehse and Jungk, 1983).…”
Section: Root Hair Length and Densitymentioning
confidence: 99%
“…The relatively short time from inoculation to production of detectable nodules makes it much easier to use than the red clover and lucerne systems (17,22,23). The highly efficient nodulation removes the necessity for large numbers of plants for a single treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Before nodulation, the surface of the root is covered with a matrix of bacteria (7). Groups of bacteria at the tips of roots have also been noted (23,25 various legumes. This work is also concerned with both nodulation and effectiveness of nitrogen fixation.…”
mentioning
confidence: 94%